2019
DOI: 10.1101/676866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motility induced fracture reveals a ductile to brittle crossover in the epithelial tissues of a simple animal

Abstract: 8Animals are characterized by their movement, and their tissues are continuously subjected to dynamic force loading while they crawl, walk, run or swim 1 . Tissue mechanics fundamentally determine the ecological niches that can be endured by a living organism 2 . While epithelial tissues provide an important barrier function in animals, they are subjected to extreme strains during day to day physiological activities, such as breathing 1 , feeding 3 , and defense response 4 . However, failure or inability to wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The existence of bistability between configurations having small spaces between cells and configurations with large extracellular 'holes', could lead to hysteretic behavior and discontinuous transitions between these states if cells in tissues slowly change control parameters (average cortical tension or adhesion) during development. While most embryonic tissues likely avoid this regime, as it could lead to epithelial fracture and loss of its barrier function, recently reported dynamics and fracture of epithelial monolayers in the organism Trichoplax Adhaerens display features of this structural transition 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The existence of bistability between configurations having small spaces between cells and configurations with large extracellular 'holes', could lead to hysteretic behavior and discontinuous transitions between these states if cells in tissues slowly change control parameters (average cortical tension or adhesion) during development. While most embryonic tissues likely avoid this regime, as it could lead to epithelial fracture and loss of its barrier function, recently reported dynamics and fracture of epithelial monolayers in the organism Trichoplax Adhaerens display features of this structural transition 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in biological physics frequently involve the detection and center of mass tracking of agents, cells, or whole organisms with image data (5,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Classroom activities that teach undergraduate students basic con-cepts in object detection and center of mass tracking of isolated agents-without requiring advanced computational image analysisequip students with the necessary foundation for thinking about quantifying motion without overwhelming them with technical difficulties.…”
Section: A Scientific and Pedagogical Backgroundmentioning
confidence: 99%
“…Active discrete systems have remarkable properties, including the capacity for learning (8,9), classification/reconstruction (10), adaptation (11)(12)(13), action at a distance (14) and regulation (15,16). For example, within the domain of biological systems, it has been demonstrated that activity is capable of significantly altering the yield stress of cellularized materials, influencing tissue shape during embryo development and driving many different self-assembly processes in vivo (13,(17)(18)(19). However, significant complexity arises from biochemical feedback processes in such systems.…”
Section: Introductionmentioning
confidence: 99%